Respuesta :
Answer:
-4x^2-6x+6
(third choice)
Step-by-step explanation:
To do f(x)-g(x) we must insert the expression for f(x) and g(x) into this:
This will give us:
(8x^2-2x+3)
-(12x^2+4x-3)
--------------------
-4x^2-6x+6
Horizontally if you prefer:
(8x^2-2x+3)-(12x^2+4x-3)
Distribute and get rid of paranthesis:
8x^2-2x+3-12x^2-4x+3
Pair up like terms:
8x^2-12x^2-2x-4x+3+3
Combine the like terms:
-4x^2-6x+6
Answer:
h(x) = -4x^2 - 6x + 6
Step-by-step explanation:
f(x) - g(x)
= 8x^2 - 2x + 3 - (12x^2 + 4x - 3) (Note the parentheses around g(x))
Distributing the negative over the parentheses:
= 8x^2 - 2x + 3 - 12x^2 - 4x + 3
= -4x^2 - 6x + 6 = h(x).